2018
DOI: 10.4274/mirt.37450
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected False-positive I-131 Uptake in Patients with Differentiated Thyroid Carcinoma

Abstract: Objective:Radioiodine is the most specific radionuclide for differentiated thyroid carcinoma (DTC) imaging. Despite its high specificity and sensitivity, false-positive I-131 uptake could be seen on whole body scan (WBS) that may lead to misdiagnosis and unnecessary radioiodine treatment. In this study, we aimed to present the I-131 WBS and concomitant single photon emission computed tomography/computed tomography (SPECT/CT) images of unexpected false-positive radioiodine uptake along with the patients’ clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Overall, the literature showed 145 case reports and two series regarding false-positive 131 uptake after RIT For the reasons stated above, we excluded 129 papers, considering only those in which SPECT/CT was performed. A total of 18 papers were thus included: 1 series [17] and 17 case reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The series reported 23 cases of falsepositive results: 15 in the chest, six in the pelvis, one in the cranium, and one in the abdomen.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the literature showed 145 case reports and two series regarding false-positive 131 uptake after RIT For the reasons stated above, we excluded 129 papers, considering only those in which SPECT/CT was performed. A total of 18 papers were thus included: 1 series [17] and 17 case reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The series reported 23 cases of falsepositive results: 15 in the chest, six in the pelvis, one in the cranium, and one in the abdomen.…”
Section: Resultsmentioning
confidence: 99%
“…Garger et al showed that the incidence of ptWBS false-positives is around 73 % with predominance for focal uptake. The etiology of false-positive uptakes cannot be determined in one-third of patients [17,30]. Accordingly, we analyzed ptWBS after the first activity of RAI and found five false-positive results patterns.…”
Section: Discussionmentioning
confidence: 97%
“…Post-treatment whole body scans (ptWBS) are currently recommended in patients receiving RAI therapy. However, the accuracy of DX-WBS for identification of metastasis is controversial (36,37). Nava et al reported a sensitivity of 29% and a specificity of 97% for DX-WBS in ATA low-intermediaterisk DTC patients, indicating it should be reconsidered for routine DX-WBS in this subgroup (38).…”
Section: Discussionmentioning
confidence: 99%